Application of Raman Spectroscopy to the Biooxidation Analysis of Sulfide Minerals. (3rd January 2012) - García-Meza, J. V.; Lara, R. H.; Navarro-Contreras, H. R.
Abstract : We report the application of confocal laser scanning microscopy CLSM and Raman spectroscopy on the (bio)chemical oxidation of pyrite and chalcopyrite, in order to understand how surface sulfur species (S n 2 - / S 0 ) affects biofilm evolution during mineral colonization by Acidithiobacillus thiooxidans . We found that cells attachment occurs as cells clusters and monolayered biofilms within the first 12 h. Longer times resulted in the formation of micro- and macrocolonies with variable cell density and higher epifluorescence signal of the extracellular polymeric substances (EPS), indicating double dynamic activity of A. thiooxidans : sulfur biooxidation and biofilm formation. Raman spectra indicatedS n 2 - / S 0 consumption modification during biofilm evolution. Hence, cell density increase was primarily associated with the presence ofS 0 ; the presence of refractory sulfur species on the mineral surfaces does not to affect biofilm evolution. The EPS of the biofilms was mainly composed of extracellular hydrophobic compounds ( vr. gr. lipids) and a minor content of hydrophilic exopolysaccharides, suggesting a hydrophobic interaction between attached cells and the altered pyrite and chalcopyrite.